A Conceptual Model for the Integrated Policy Framework - Basu, Suman; Boz, Emine; Gopinath, Gita.; Roch, Francisco (Washington, D.C. : International Monetary Fund, 2020)
In the Mundell-Fleming framework, standard monetary policy and exchange rate flexibility fully insulate economies from shocks. However, that framework abstracts from many real world imperfections, and countries often resort to unconventional policies to cope with shocks, such as COVID-19. This paper develops a model of optimal monetary policy, capital controls, foreign exchange intervention, and macroprudential policy. It incorporates many shocks and allows countries to differ across the currency of trade invoicing, degree of currency mismatches, tightness of external and domestic borrowing constraints, and depth of foreign exchange markets. The analysis maps these shocks and country characteristics to optimal policies, and yields several principles. If an additional instrument becomes available, it should not necessarily be deployed because it may not be the right tool to address the imperfection at hand. The use of a new instrument can lead to more or less use of others as instruments interact in non-trivial ways.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet